The Importance of Effective Communication in Supporting Teacher Empowerment in Schools: A Literature Reviews - Iano, Taufik Ridho; Hadiyanto, Hadiyanto; Sulastri, Sulastri (International Journal of Educational Dynamics, 2024)
Effective communication is a key element in fostering synergy among teachers, principals, and the broader educational community. This article aims to examine the importance of effective communication in supporting teacher empowerment within schools. Using a literature review method, this study explores the concept of effective communication, its strategic role in enhancing teacher engagement, and its impact on educational success. Findings from various literature analyses reveal that effective communication in teacher empowerment is essential for improving work effectiveness in teaching activities, such as fostering teachers' creative ideas, conducting teacher training, facilitating communication in discussion groups, and simplifying the delivery of teaching materials to students. This study also highlights that effective communication not only serves as a tool for transmitting information but also functions as a medium for sharpening creativity, solving problems, and enhancing competencies, particularly for teachers. In the context of empowerment, strategic communication helps address common challenges faced by educators. Therefore, continuous efforts are necessary to enhance communication skills at all levels of school management to achieve optimal teacher empowerment.